What are the causes of different brain drain rates in emerging markets? An exploratory study of Brazil and Mexico - Hauer, Adriane Louise Frieda (2018)
The following Master’s thesis examines the causes of brain drain in the context of emerging countries. More precisely, the thesis aims to assess to what extent the migration of highly educated people from emerging countries can be explained by labor market conditions, as neoclassical economics claim. Labor market conditions are defined as job opportunities and income. Mexico and Brazil have been used as case studies due to their similar socioeconomic characteristics. The thesis first provides an overview of the theoretical background of international migration and brain drain. Based on this review, a framework is created. Followed by that a PESTLE analysis is given, which helps to understand the primary data results. Primary data was collected from a sample with 140 participants of each country. In the analysis of the primary data, the Master’s thesis shows that labor market conditions do play an influential role in the decision-making process to move abroad permanently, but only in the context of other factors. Some of those factors have a much stronger influence, such as lifestyle and social ties.